Palaeoecology and vegetation dynamics in the Cederberg wilderness area - Ballantyne, Fiona (Department of Biological Sciences, 2014)
The Cederberg Wilderness Area, in the Cape Floristic Region, South Africa, contains over 2000 plant species, 280 of which are endemic. The area has been subject to various forms of land use for millennia ranging from hunter-gatherers, herders, and farmers to visitors today. This study used palaeoecological techniques to investigate the impacts of past land use, specifically the transition from hunter-gathering to farming and herding in order to provide a baseline for current wilderness management. A sediment core was extracted from a wetland adjacent to the De Rif farmstead, analysed for fossil pollen and charcoal and dated using AMS radiocarbon dating. Historical records were used to link changes with land use history. A vegetation survey of the site focussed on the grass component of the vegetation. The largest impacts on vegetation during the last 2300 years are due to grazing and agriculture during the 1800s to 1940. Fire-sensitive taxa have not declined, apart from possibly Ericaceae, suggesting that changes in fire have not exceeded a threshold that affects the community at a family level. Changes in the fire regime, combined with disturbance by ploughing and grazing have increased the abundance of Poaceae and Cyperaceae, resulting in a decrease in Restionaceae. Ploughing affected the height structure and species composition of the site, and allowed the invasion and persistence of exotic grasses which now make up 43% of total grass cover on the previously ploughed area. Few indigenous fynbos grasses were found suggesting that the grass community is depauperate due to disturbance. The higher grass abundance preceded the largest fire recorded in the charcoal record suggesting a grass fire cycle has started at De Rif. Ploughing, grazing and invasive grasses, rather than changes in fire regime or resource extraction, are the main causes of vegetation change at De Rif and still affect the site today. Wilderness management will need to mitigate the impacts of livestock and agriculture on De Rif and monitor the recovery of this and other previously farmed areas to ensure that they do not become as a source of invasive species in the future under novel disturbances such as anthropogenic climate change.